Environmental Friendly Alternative Methods for the Recovery of Intracellular Polyhydroxyalkanoates (PHA) - Voon, Pooi Tee (2005)
Polyhydroxyalkanoates (PHA) are intracellular polymers that can be produced by bacteria as energy reserve material. This biodegradable material has properties similar to synthetic thermoplastics. However, the process recovery of PHA using organic solvents such as chloroform is expensive and not environmental-friendly. Although most of the organic solvent is recovered for reuse, it still causes serious damage to health and environment. Thus, alternative methods that are environmental-friendly are needed for the recovery of PHA. Fermentation was carried out using a 50 L bioreactor at pH 7, 30°C, with agitation speed of 200 rpm and 1 vvm aeration rate to maintain aerobic condition. Ralstonia eutropha ATCC 17699 was chosen as the PHA production bacteria. Twenty g/L mixture of acetic and propionic acids were fed into the broth as carbon sources and PHA was produced in nitrogen limited condition with C/N = 50. Cells were harvested by centrifugation and the pellets were then dried in oven at 60°C, grinded and stored at 4OC for recovery of PHA. Biomass containing PHA with the concentration of 0.32 glg biomass was treated with various chemicals such as alkaline solutions (NaOH, KOH), surfactants (sodium dodecyl sulfate or SDS, sodium salt of a-sulfonate methyl esters derived from palm stearin or a-SMEPS, Tween 20, Tween 80 and betaine anhydrous) and enzyme (lysozyme) to digest non-PHA cellular material (NPCM) at dried cells concentration of 5 g/L. Mechanical methods such as ultrasonic sonication and homogenization were also used for further cell disruption. Combined treatment of alkali and homogenization was also investigated. After treatment, PHA granules were separated from cell debris by centrifugation at 3500 rpm for 10 min. PHA granules recovered were rinsed twice with deionized water to avoid floatation, centrifuged and air-dried. Pellet was analyzed by using HPLC and supernatant was analyzed by the presence of protein. Combined treatment of NaOH and homogenization were found to give the highest PHA purity and yield of 97% and 94%, respectively, compared to other methods. The purity of the final PHA increased with the released of cellular protein. PHA could be recovered from biomass by combined NaOH pretreatment, (0.2 M, 60 min) and homogenization (18 min) to achieve cell disruption. This method is simple, economical, environmental friendly, non-toxic and suitable for larger scale production. The product obtained was white in colour and ready to be accepted by end user for commercialization. Thus, combined NaOH treatment and homogenization can replace chloroform for the recovery of PHA.